A rosin-functionalized plastic surface inactivates African swine fever virus - Hemmink, Johanneke Dinie; Shroff, Sailee; Chege, Naomi; Haapakoski, Marjo; Dixon, Linda K.; Marjomäki, Varpu (Frontiers in Veterinary Science, 2024)
African swine fever virus (ASFV) causes a severe hemorrhagic disease in pigs, leading to up to 100% case fatality. The virus May persist on solid surfaces for long periods; thus, fomites, such as contaminated clothing, footwear, farming tools, equipment, and transport vehicles, May contribute to the indirect transmission of the virus. Here, a plastic surface functionalized with tall oil rosin was tested against ASFV. The rosin-functionalized plastic reduced ASFV infectious virus titers by 1.3 log10 after 60 min of contact time and killed all detectable viruses after 120 min, leading to a ~ 6 log10 reduction. In contrast, the infectious virus titer of ASFV in contact with low-density polyethylene (LDPE) plastic reduced <1 log10 after 120 min. Transmission electron microscopy (TEM) showed significant morphological changes in the virus after 2 h of contact with the rosin-functionalized plastic surface, but no changes were observed with the LDPE plastic. The use of antiviral plastic in the farming sector could reduce the spread of ASFV through fomites and could thus be part of an integrated program to control ASFV.